Utility of a genetic risk score to predict recurrent cardiovascular events 1 year after an acute coronary syndrome: A pooled analysis of the RISCA, PRAXY, and TRIUMPH cohorts. Issue 1 (September 2015) - Labos, Christopher; Martinez, Sara C.; Leo Wang, Rui Hao; Lenzini, Petra A.; Pilote, Louise; Bogaty, Peter; Brophy, James M.; Engert, James C.; Cresci, Sharon; Thanassoulis, George
Abstract: Background: Limited evidence exists regarding the utility of genetic risk scores (GRS) in predicting recurrent cardiovascular events after acute coronary syndrome (ACS). We sought to determine whether a GRS would predict early recurrent cardiovascular events within 1 year of ACS. Methods & Results: Participants admitted with acute coronary syndromes from the RISCA, PRAXY, and TRIUMPH cohorts, were genotyped for 30 single nucleotide polymorphisms (SNPs) associated with coronary artery disease (CAD) or myocardial infarction (MI) in prior genome wide association studies. A 30 SNP CAD/MI GRS was constructed. The primary endpoint was defined as all-cause mortality, recurrent ACS or cardiac re-hospitalization within 1 year of ACS admission. Results across all cohorts for the 30 SNP CAD/MI GRS were pooled using a random-effects model. There were 1040 patients from the RISCA cohort, 691 patients from the PRAXY cohort, and 1772 patients from the TRIUMPH cohort included in the analysis and 389 occurrences of the primary endpoint of recurrent events at 1-year post-ACS. In unadjusted and fully adjusted analyses, a 30 SNP GRS was not significantly associated with recurrent events (HR per allele 0.97 (95%CI 0.91–1.03) for RISCA, HR 0.99 (95%CI 0.93–1.05) for PRAXY, 0.98 (95%CI 0.94–1.02) for TRIUMPH, and 0.98 (95%CI 0.95–1.01) for the pooled analysis). Addition of this GRS to the GRACE risk model did not significantly improve risk prediction. Conclusion: The 30 MI SNP GRS was not associated with recurrent events 1-year post ACS in pooled analyses across cohorts and did not improve risk discrimination or reclassification indices. Our results suggest that the genetic etiology of early events post-ACS may differ from later events. Highlights: A genetic risk score of 30 MI SNPs is not associated with early recurrent events post MI. When added to the GRACE risk score, a genetic score does not improve risk prediction for recurrent events post-ACS. No individual SNPs were consistently associated with recurrent events across all 3 cohorts.